IMPLEMENTATION OF INERTIAL MEASUREMENT UNIT SENSOR IN VSAT ANTENNA DIRECTION MONITORING SYSTEM USING LORA MODULE - Herfiah, Shita; Nizaar Alpudli, Faiz (Universitas Lampung, 2025)
The Very Small Aperture Terminal (VSAT) antenna is a crucial component in satellite communication that requires accurate orientation to maintain signal quality. Orientation changes due to impacts, vibrations, or weather conditions can degrade signal performance. This study designs a real-time antenna angle monitoring system based on the Internet of Things (IoT) using an Inertial Measurement Unit (IMU) sensor, the MPU-9250. The system consists of a transmitter node and a receiver node. The transmitter node detects the antenna's elevation and azimuth angles using the MPU-9250 and sends the data via the LoRa SX1276 915 MHz module to the receiver node. The receiver node, equipped with an ESP32, sends the data to the Firebase Realtime Database and automatically delivers notifications via a Telegram bot when a directional change is detected. Testing results show that the MPU-9250 accurately detects angle changes, indicated by increased Signal Quality Factor (SQF) values when the antenna is in its optimal position. LoRa communication remains stable up to 20 meters, with a significant signal quality drop beyond 25 meters. The system effectively monitors and alerts directional changes of the antenna in real time, helping to maintain optimal satellite communication connectivity.